2020
DOI: 10.1152/ajpgi.00278.2020
|View full text |Cite
|
Sign up to set email alerts
|

Role of an active reserve stem cell subset of enteroendocrine cells in intestinal stem cell dynamics and the genesis of small intestinal neuroendocrine tumors

Abstract: Small intestinal neuroendocrine tumors (SI-NET) are serotonin-secreting well-differentiated neuroendocrine tumors of putative enterochromaffin (EC) cell origin. Recent studies recognize a subset of EC cells that is label-retaining at the +4 position in the crypt and functions as a reserve intestinal stem cell (ISC). Importantly, this +4 reserve EC cell subset not only contributes to regeneration of the intestinal epithelium during injury and inflammation but also to basal crypt homeostasis at a constant rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Our current hypothesis is that a subset of EC cells residing at +4 position in the crypt with active reserve stem cell function are the origin of SI-NETs and account for the genesis of the multifocal and polyclonal tumors observed in familial disease. 24 This study of crypts from ileal biopsy specimens supports our previous observation of the widespread, multifocal nature of familial tumors. Furthermore, the early accumulation of EC cells below +4 position at the crypt bottom demonstrated in our study offer the potential basis for the diagnostic screening value of whole-mount crypt analysis of ileal biopsy specimens for at risk members of families with SI-NETs.…”
Section: Discussionsupporting
confidence: 89%
“…Our current hypothesis is that a subset of EC cells residing at +4 position in the crypt with active reserve stem cell function are the origin of SI-NETs and account for the genesis of the multifocal and polyclonal tumors observed in familial disease. 24 This study of crypts from ileal biopsy specimens supports our previous observation of the widespread, multifocal nature of familial tumors. Furthermore, the early accumulation of EC cells below +4 position at the crypt bottom demonstrated in our study offer the potential basis for the diagnostic screening value of whole-mount crypt analysis of ileal biopsy specimens for at risk members of families with SI-NETs.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, ChgA + EECs with high levels of Sox9 expression exhibit regenerative capacity following irradiation [139,140]. Consistent with these observations, another study demonstrates that a subset of EECs is able to dedifferentiate into ‘reserve ISCs’ in response to radiation‐induced injury [141].…”
Section: Eecs Mediate Intra‐ and Interorgan Communication To Modulate...mentioning
confidence: 83%
“…Moreover, there is no known genetic defect that associates with ileal NENs, even though jejunal NETs have been reported in patients with MEN1 syndrome [67][68][69]. Recently, Sei et al [70] have suggested the existence of a multiphasic carcinogenetic process in SI-NETs, studying a family with a par-ticular genetic alteration. According to their results, SI-NETs originate from a peculiar type of serotonin-producing enterochromaffin cell (EC) that retains the capability to dedifferentiate and acquire stem properties [71].…”
Section: Jejunum and Ileummentioning
confidence: 99%
“…Abnormal crypts with micronodules of chromogranin A-positive ECs (i.e., aberrant crypt containing endocrine cell clusters [ACECs]) widely distributed in the macroscopic tumor-free mucosa were detected. Moreover, clusters of EECs in ACECs seem to express typical ARISC marker genes, such as BMI1 and HOPX [70]. Globally, these results suggest that ARISCs and ACECs may be precursors of SI-NETs.…”
Section: Preneoplastic Lesions Of Gep-nens Listed By Anatomical Sitementioning
confidence: 99%